Myopia in Children: Epidemiology, Genetics, and Emerging Therapies for Treatment and Prevention - Pier Luigi Surico; Uday Pratap Singh Parmar; Rohan Bir Singh; Yeganeh Farsi; Mutali Musa; Antonino Maniaci; Salvatore Lavalle; Fabiana D’Esposito; Caterina Gagliano; Marco Zeppieri (Children)
Refractive errors, particularly myopia, are among the most prevalent visual impairments globally, with rising incidence in children and adolescents. This review explores the epidemiology and risk factors associated with the development of refractive errors, focusing on the environmental and lifestyle factors contributing to the current surge in myopia. We provide an overview of key genetic factors and molecular pathways driving the pathogenesis of myopia and other refractive errors, emphasizing the complex interplay between genetic predisposition and environmental triggers. Understanding the underlying mechanisms is crucial for identifying new strategies for intervention. We discuss current approaches to slow myopia progression in pediatric populations, including pharmacological treatment regimens (low-dose atropine), optical interventions, and lifestyle modifications. In addition to established therapies, we highlight emerging innovations, including new pharmacological agents and advanced optical devices, and insights into potential future treatments. Cutting-edge research into gene therapy, molecular inhibitors, and neuroprotective strategies may yield novel therapeutic targets that address the root causes of refractive errors. This comprehensive review underscores the importance of early intervention and highlights promising avenues for future research, aiming to provide pediatricians with guidance to ultimately improve clinical outcomes in managing and preventing myopia progression in children and young adults.